VIA: reportagem hipermídia sobre mulheres refugiadas no estado de São Paulo - Mela, Amanda Casagrande [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
This Term Paper had as a goal understand and discuss the gender issues inside the vulnerability situation in which the refugees have been living, given that there are few papers about it that address gender cutbacks. Through the development of a serie of hypermedia reports about female refugees in the state of São Paulo, the purpose is to give visibility to these women in a way that clearly shows that the refuge is a surviving situation. With an implementation methodology, interviews, documentary research and data survey were used to achieve the goal. As a result, we introduce several hypermedia longform reports, which approach the contextualization of the refugees situation around the world and in the state of São Paulo; the institutions and NGOs dedicated to these subject; the cultural identity of these women; their mental health and, finally, the female refugees profile

Este Projeto de Conclusão de Curso teve como proposta compreender e discutir as questões de gênero dentro da situação de vulnerabilidade vivida pelas refugiadas, visto que ainda existem poucos trabalhos sobre o tema que envolvem recorte de gênero, por meio do desenvolvimento de uma série de reportagens hipermídia sobre mulheres refugiadas no estado de São Paulo. O objetivo é dar visibilidade às mulheres refugiadas, de modo que fique evidente que o refúgio é uma condição de sobrevivência. Como metodologia de execução foram utilizadas entrevistas, pesquisa documental e levantamento de dados. Como resultado é apresentada uma série de reportagens hipermídia longform, que abordam a contextualização sobre o histórico do refúgio no mundo, no Brasil e no estado de São Paulo; instituições e ONGs de assistências aos refugiados; a questão da identidade cultural e saúde mental na situação de refúgio e; por fim, perfis de mulheres refugiadas
Keywords: Refugiados - São Paulo; Mulheres; Imigrantes; Refugees